Effects of rest duration between sets of resistance training on acute hormonal responses in trained women - Bottaro, M.; Martins, B.; Gentil, P.; Wagner, D. (Journal of Science and Medicine in Sport, 2009)
This study investigated the acute hormonal response to three different rest periods between sets of a traditional lower body resistance training session in young women. Twelve healthy trained females (26.83 ± 3.93 years) participated in the study. On three separate sessions of a lower body resistance exercise protocol, subjects were assigned in a random order a rest interval of 30 s (P30), 60 s (P60) or 120 s (P120) between sets. The resistance exercise session consisted of four lower body exercises with three sets performed until contractile failure using 10-repetition maximum (RM) load. Blood samples were drawn for determination of serum growth hormone (GH) and cortisol concentrations before exercise (T0), immediately after each training session (T1), and after 5 min (T5), 15 min (T15), and 30 min (T30) of recovery. Statistical evaluation of the area under the time-concentration relationship for GH (GHauc) and for cortisol (Cauc) were analyzed using a one-way ANOVA There were no differences among protocols (P30, P60 and P120) in the serum GH and cortisol concentrations at baseline (T0). However, as compared to T0, all protocols led to acute increases (p < 0.05) in serum GH concentrations after each training session. The GHauc was greater for P30 than for both P60 and P120, however, there were no differences between P60 and P120. The Cauc were not different among protocols. Thus, the magnitude of acute GH responses in previously strength-trained women appears greater with a 30-s rest interval between sets compared to longer rest periods of 60- or 120-s.